Telaah Mendalam tentang Worldview: Perspektif dan Signifikansinya dalam Kehidupan Sehari-hari - Mujahid, Kasori; Sangadah, Siti (TSAQOFAH, 2025)
This article discusses the concept of worldview and its significance in daily life, explaining how worldview shapes an individual's understanding of the world. The research highlights the influence of worldview on beliefs, values, and behaviors of individuals in daily life, using a descriptive qualitative approach. Data collection is carried out through observation, interviews, and documentation. The study encourages readers to reflect on and explore the implications of worldview in daily life. It emphasizes the importance of understanding the worldview of others to enhance tolerance, cross-cultural understanding, and global collaboration.